The Effect of Sustainability Performance on Corporate Financing Policy in Asean-5 Countries - Suzandry, Tri Vita; Hermawan, Ancella A. (Indonesian Journal of Economics and Management, 2024)
This research empirically studied the effect of sustainability performance on financing policy, in five ASEAN countries. Sustainability performance disclosure activities are becoming increasingly crucial for businesses, including ASEAN countries. This study aimed to examine the impact of sustainability performance (ESG Scores) on debt-to-equity ratio (DER) as a proxy for corporate financing policy. This study used panel data analysis. This study obtained a sample of public companies listed on each exchange in ASEAN-5 (Indonesia, Philippines, Malaysia, Singapore, and Thailand) with a period of 2016 to 2021. The results showed that ESG had a negative substantial effect on the debt-to-equity ratios of ASEAN-5 enterprises, which means that companies with good ESG scores will rely more on equity than debt. The results of the study are expected to assist companies in continuing to improve sustainability performance and evaluating ESG performance to create the proper views and analyses to develop financing policy (capital structure) in ASEAN-5 enterprises.